Perilaku Dan Sikap Karakteristik Serta Ekonomi Masyarakat Pesisir di Dusun XIV Desa Percut - Fitria, Adinda Dwi; Khetri, Anggina Cucu; Salwa, Fadillah; Haridani, Hifza; Manik, Hubban Fathani; Khairani, Khovifah; Dasopang, Lailatul Mahpuja; Lestari, Ninis; Rahmawati, Nurul; Sagala, Shinny Syafitri; Arika, Romiza (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Coastal communities are people who live and live in coastal areas, namely transitional areas that mark the place of movement between land and sea areas or vice versa, where most of the people live from managing coastal and marine resources, either directly or indirectly. social characteristics that are firm, hard, and open. Coastal communities live as fishermen who depend on resources that are open access (sea) for their livelihood. The sea as the main resource for fishing is influenced by the climate, which is often irregular and high risk. Keywords: Community, Region, Characteristics